Analisis Performa Dies Blank pada CV. ABC Menggunakan Metode Overall Equipment Effectiveness (Oee) dan Failure Mode and Effect Analysis (FMEA) - Nenden Septihani; Elvira Firdayanti; Imanuel Christiawan Prasetyo; Tiaradia Ihsan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
CV. ABC, a tier-3 metal component manufacturer for motorcycles, faces productivity decline due to frequent blank die failures in seat lock plate production, exacerbated by conventional machines and material variations like SPHC and SK85. This study aims to analyze blank die performance and identify critical failure causes using Overall Equipment Effectiveness (OEE), Fishbone Diagram, and Failure Mode and Effect Analysis (FMEA). Employing a quantitative descriptive case study design, the population comprised all blank die operations in October, with a purposive sample of 24 workdays (one shift, 10 hours/day). Instruments included observation sheets for production data and semi-structured interviews; analysis involved OEE calculations, root cause mapping, and RPN computation. Results show OEE at 75.55% (below Nakajima's 85% standard), with availability 90.91%, performance 87.72%, quality 94.73%, and downtime losses of 8,820 units. Fishbone analysis revealed six failure aspects, while FMEA prioritized punch dies (RPN 360), dies (288), and punch piercing (256). In conclusion, focused maintenance on critical components will enhance productivity and replicability in similar industries.